Symplocos buxifolia - Tsen, S.; Matusin, D.; Khoo, E.; Maryani, A.; Colin Ruzelion Maycock; Nilus, R.; Sugau, J.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2021)
Symplocos buxifolia is a small tree, endemic to Sabah. The estimated area of occupancy (AOO) and extent of occurrence (EOO) are both 32 km2. Although the AOO is calculated from known existing records, it is considered that the actual AOO may be considerably larger than this due to under sampling. It is found scattered around Mount Kinabalu, and currently facing no major threat to its population. It is assessed as Least Concern. Symplocos buxifolia is endemic to Sabah, Malaysia. It is known from Mount Kinabalu.